The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3855/jidc.1248
|View full text |Cite
|
Sign up to set email alerts
|

The sale of antibiotics without prescription in pharmacies in Damascus, Syria

Abstract: Introduction: Overuse of antibiotics has contributed to the development of organism resistance. The acquisition of antibiotics without prescription by the general population seems to be common practice in pharmacies of Damascus, Syria. This study aimed to determine the proportion of pharmacies dispensing antibiotics without medical prescription and without seeing the patient. Methodology: A cross-sectional study involving a sample of 224 pharmacies was conducted in Damascus. To obtain antibiotics without medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 12 publications
5
81
0
1
Order By: Relevance
“…The driving factors that determined the pharmacists practices included keeping the pharmacy business, the relationship to the pharmacist, the patient's age, and pregnancy. Some of these factors are similar to the ones we found in other Arab countries 10 ; other factors are different from the ones found in other developing countries outside of the Arab world. 5,8,9 This was clearly obvious in all the scenarios proposed to our pharmacist interviewees.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The driving factors that determined the pharmacists practices included keeping the pharmacy business, the relationship to the pharmacist, the patient's age, and pregnancy. Some of these factors are similar to the ones we found in other Arab countries 10 ; other factors are different from the ones found in other developing countries outside of the Arab world. 5,8,9 This was clearly obvious in all the scenarios proposed to our pharmacist interviewees.…”
Section: Discussionmentioning
confidence: 60%
“…An earlier study performed in the Syrian capital of Damascus found an alarming percentage of 89.3% of antibiotics are sold without a prescription. 10 Existing regulations do not include antibiotics as one of the categories of medications that can be dispensed without a prescription, however, there is no clear or strict regulations prohibiting the direct sale of antibiotics without a prescription. 14 All interviewed pharmacists felt comfortable dispensing antibiotics without a prescription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional client simulation study in Syria, 87% of the pharmacies sold antibiotics without a prescription. This proportion increased up to 97% when the client simulators insisted on buying antibiotics [19]. Similar studies in Saudi Arabia and India had comparable results: 78% and 94% of visited pharmacies dispensed over the counter antibiotics [20,21].…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, before the Syrian war, prevalence of ESBL urinary tract infections associated with wide use of antimicrobial drugs was high ( 6 ). In addition, sale of antimicrobial drugs without prescriptions was common in Damascus and other areas ( 7 ). The war added inadequate sanitation, hospital and infrastructure destruction, and suboptimal infection control measures.…”
mentioning
confidence: 99%